The Swedish textile conservators' transformation: From the museum curator's assistant to a profession in its own right. Issue 2 (19th July 2021) - Nilsson, Johanna M; Blume, Katarina S
Abstract: Over recent years, in Sweden, the vocation of textile conservator has been transformed from that of being regarded simply as a museum curator's assistant to becoming a profession in its own right. The members of the textile conservators association, the Swedish Association for Textile Conservation founded in 1967, played a crucial role in this transformation with the establishment of a university-based vocational education programme in 1985. The transformation is further scrutinized by considering aspects of gender where, for example, gender bias employment strategies favoured men as painting conservators, as well as social class where demarcation of women as curators was evident. This is discussed and compared with the contemporary shift of gender distribution among the employees in the museum sector that historically was largely male dominated. Social class and the effects of a university education on occupational status are considered, and the effects that education had on elderly, experienced colleagues are another important intersectional aspect. Today's textile conservators have reached a professional status in several aspects with university education being probably the most important contributing factor. The image of the vocation has improved from that of a seamstress who performed repairs on textiles at the direction of her superior, to an academic who, on the basis of their scientific knowledge, independently performs the many tasks included in preservation, as well as conducting research to doctorate level. Despite this, it would seem that the museum community has not yet managed to take full advantage of textile conservators' competence as researchers.